RETRACTED: The impact of the green economy on the sustainable development of Kazakhstan - Berstembayeva Rysty; Niyazbekova Shakizada; Tleuzhanova Danagul; Varzin Vasiliy (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001